Google sites-based math book development on statistical materials to improve students' understanding of mathematical concepts - Buchori, Achmad; Aryani, Desy Dwi; Kusumaningsih, Widya (Universitas Islam Raden Intan Lampung, INDONESIA, 2023)
Background: The learning process in mathematics significantly impacts students' comprehension, particularly due to the scarcity of practical learning tools for understanding mathematical concepts. This challenge has led researchers to focus on developing innovative and practical learning media to enhance students' grasp of these concepts.Aim: This study aimed to determine the effectiveness of a math book based on Google Sites, assessing its validity, practicality, and impact on students' understanding of mathematical concepts.Method: The Research and Development (R&D) approach was employed using the ADDIE model, which includes Analysis, Design, Development, Implementation, and Evaluation. The study involved 61 students, with 30 from class VII D as the experimental group and 3